AMP579 is revealed to be a potent A(2b)-adenosine receptor agonist in human 293 cells and rabbit hearts - Liu, Yanping (2010)
The mixed A(1)/A(2a)-adenosine agonist AMP579 given at reperfusion is protective in animal models of myocardial infarction. Receptor-blocking studies have indicated that the protection came from an adenosine receptor (AR), but neither A(1)- nor A(2a)-selective agonists could duplicate its protection. We recently found that A(2b)-selective agonists given at reperfusion are protective, and, therefore, tested whether AMP579 might also be an A(2b) agonist. We used human embryonic kidney cells overexpressing human A(2b) receptors as an assay system. In these cells, A(2b) receptor occupancy causes phosphorylation of ERK. AMP579 induced ERK phosphorylation with an EC(50) of 250 nM and this phosphorylation could be blocked by MRS1754 or PSB1115, two highly selective blockers of human A(2b) receptors. We attempted to confirm our A(2b) hypothesis in a rabbit heart model of ischemia–reperfusion. AMP579 (500 nM) for 1 h starting at reperfusion reduced infarct size in isolated rabbit hearts exposed to 30 min of regional ischemia and 2 h of reperfusion (12.9 ± 2.2% infarction of risk zone vs. 32.0 ± 1.9% in untreated hearts). PSB1115 (500 nM) given for the first 15 min of reperfusion blocked AMP579’s protection (32.2 ± 3.1% infarction) which is consistent with an A(2b) mechanism. We conclude that AMP579 is a non-selective, but potent A(2b)-AR agonist, and that its protection against infarction is through that receptor.